Fast-curing modified polydicyclopentadiene resin as well as preparation method and application thereof
By configuring the catalyst and anhydride curing epoxy resin, the modified polybicyclopentadiene resin is prepared, which solves the problems of long molding cycles and insufficient heat resistance of traditional composite materials, achieves rapid curing and high heat resistance, and improves the bonding strength with fibers.
Patent Information
- Application Number
- CN202311431170.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
AI Technical Summary
The traditional molding cycle of existing high-performance fiber/thermoset resin composites is relatively long and cannot meet the manufacturing time requirements of automobile production lines. At the same time, there is a contradiction between the heat resistance and curing time of polycyclopentadiene resin, and the combination with fibers is insufficient.
By configuring the catalyst solution of Grubbs second generation catalyst, tributyl phosphite and cyclohexylbenzene and dicyclopentadiene or norbornene-dicyclopentadiene mixture, the epoxy resin is cured in combination with acid anhydride, and the modified polybicyclopentadiene resin is prepared, and cured and heat treated by wet molding process.
The rapid curing of the modified polybicyclopentadiene resin is achieved, with a short curing time and high heat resistance. It can reach a curing degree of 90-95% within 3 to 5 minutes under 60℃ to 90℃, and completely cured under 120℃ to 150℃. At the same time, the bonding strength with the fiber is improved, and the glass transition temperature is greater than 130℃.
Smart Images

Figure BDA0004523691040000031 
Figure BDA0004523691040000041
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a fast-curing modified polydicyclopentadiene resin and a preparation method and application thereof. Background Art
[0002] With the increasing global warming and pollution, how to reduce automobile fuel consumption has become a global issue. In this context, lightweight technology is of great significance to the future development of the automotive industry. Compared with other lightweight materials, high-performance continuous fiber reinforced composites have become the first choice for lightweight materials due to their light weight, high strength, corrosion resistance, fatigue resistance, and easy overall molding. However, the traditional molding cycle of high-performance fiber / thermosetting resin composites is long (several hours), which is far from meeting the manufacturing time requirements of automobile production lines (several minutes), which largely restricts the large-scale application of composite materials in the automotive field. Therefore, the development of a fast-curing resin system is the basis for realizing the large-scale application of carbon thermosetting composites in the automotive field.
[0003] Polydicyclopentadiene (PDCPD) is a new type of thermosetting resin with both rigidity and toughness. It is obtained by ring-opening metathesis polymerization (ROMP) of dicyclopentadiene (DCPD) catalyzed by organic metal. Since the viscosity of DCPD monomer is relatively low (less than 10mPa·s at room temperature), once the reaction is initiated after the addition of the catalyst, the polymerization can be completed in a very short time (3-5min). At present, it has been used to prepare a variety of outer shells for automobile shells and other large-scale engineering equipment through reaction injection molding (RIM). Using polydicyclopentadiene as the resin matrix of thermosetting composite materials has a theoretical basis and practical engineering significance. However, the existing fast-curing PDCPD system has a low glass transition temperature (<100℃) after curing and insufficient heat resistance; the PDCPD system with a high glass transition temperature after curing has a long curing time and cannot meet the requirements of rapid prototyping.
[0004] Furthermore, polydicyclopentadiene is usually compounded with fibers to enhance the mechanical properties of the material. However, PDCPD cannot form a strong bond with the original sizing agent on the fiber surface, resulting in low mechanical properties of the prepared composite material. Studies have shown that the sizing process suitable for PDCPD resin is relatively long and cannot be industrialized in the short term. The combination of polydicyclopentadiene modified by epoxy resin cured with a small amount of anhydride and carbon fiber is currently a more feasible solution, which improves the interface bonding ability with carbon fiber without significantly increasing the curing cycle of the mixed resin. Summary of the invention
[0005] The object of the present invention is to provide a fast-curing modified polydicyclopentadiene resin and a preparation method and use thereof, so as to solve the problems of the contradiction between the heat resistance and curing time of PDCPD and the insufficient bonding with fibers in the prior art.
[0006] In order to achieve the above object, according to one aspect of the present invention, a method for preparing a fast-curing modified polydicyclopentadiene resin is provided, comprising the following steps:
[0007] (1) Preparation of polydicyclopentadiene resin system: dissolving Grubbs II catalyst and tributyl phosphite in cyclohexylbenzene to prepare a catalyst solution, and mixing the prepared catalyst solution with dicyclopentadiene or norbornene-dicyclopentadiene mixed solution;
[0008] (2) Epoxy resin system configuration: add anhydride curing agent and accelerator into epoxy resin in a certain proportion and mix thoroughly;
[0009] (3) mixing the epoxy resin system prepared in step (2) and the polydicyclopentadiene resin system prepared in step (1), mixing them evenly and storing them at room temperature to obtain the modified polydicyclopentadiene resin.
[0010] Furthermore, in the step (1), the molar ratio of the Grubbs second-generation catalyst to dicyclopentadiene is 1:5000 to 1:15000, the molar ratio of the second-generation catalyst to tributyl phosphite is 1:1 to 1:8, and the mass ratio of the second-generation catalyst to cyclohexylbenzene is 1:100 to 1:400.
[0011] Furthermore, in the step (1), the dissolution temperature of the Grubbs second-generation catalyst in cyclohexylbenzene is 40 to 60° C., and the dissolution time is 30 to 60 minutes.
[0012] Furthermore, in the step (1), the norbornene-dicyclopentadiene mixed solution contains 3% to 5% by mass of norbornene.
[0013] Furthermore, the epoxy resin in step (2) comprises one or more of bisphenol A epoxy resin, bisphenol F epoxy resin and bisphenol S epoxy resin.
[0014] Furthermore, in the step (2), the acid anhydride curing agent is selected from at least one of methyl nadic anhydride, methyl tetrahydrophthalic anhydride, methyl hexahydrophthalic anhydride and phthalic anhydride.
[0015] Furthermore, the promoter in step (2) is selected from amine promoters such as 2, 4, 6-tris(dimethylaminomethyl)phenol, benzyldimethylamine, and triethanolamine.
[0016] Furthermore, the amount of the anhydride curing agent in step (2) satisfies the following formula:
[0017] W=A e ×B×N and N=0.2~1.0,
[0018] Wherein, W is the mass of anhydride curing agent required per 100g epoxy resin, g; A e is the molar mass of the anhydride, kg / mol; B is the epoxy value of the epoxy resin; N is the amount of anhydride required per molar mass of epoxy group, mol.
[0019] Furthermore, in step (2), the amount of the accelerator is 5wt% to 10wt% of the epoxy resin.
[0020] Furthermore, in the step (3), the mass ratio of the epoxy resin system to the polydicyclopentadiene resin system is 5:100 to 10:100.
[0021] According to another aspect of the present invention, there is also provided a fast-curing modified polydicyclopentadiene resin, which is prepared by the above-mentioned preparation method.
[0022] According to another aspect of the present invention, there is also provided a use of the above-mentioned fast-curing modified polydicyclopentadiene resin in the preparation of fiber composite materials.
[0023] Furthermore, the fiber composite material includes fibers and modified polydicyclopentadiene resin cured on the fibers.
[0024] Furthermore, modified polydicyclopentadiene resin is coated on the fiber, then placed in a molding machine for pressure maintenance and curing, and then placed in an oven for heat treatment to obtain a fiber composite material, wherein the fiber is selected from at least one of carbon fiber, glass fiber, and basalt fiber, the curing is maintained at 60°C to 90°C for 3 to 5 minutes, and the heat treatment is maintained at 120°C to 150°C for 1 to 2 hours.
[0025] Compared with the prior art, the technical effects of the present invention are as follows:
[0026] The modified polydicyclopentadiene resin of the present invention has the advantages of high heat resistance, short curing time and high fiber bonding strength. The matrix resin of the modified polydicyclopentadiene resin is polydicyclopentadiene, and the modified resin is anhydride cured epoxy. The mixed resin can reach a curing degree of 90-95% in 3-5 minutes under the condition of 60-90°C, and is completely cured in 1-2 hours under the condition of 120-150°C. The modified polydicyclopentadiene resin has good interface bonding with carbon fiber, glass fiber and basalt fiber, and has the advantages of high heat resistance (glass transition temperature greater than 130°C) after curing. DETAILED DESCRIPTION
[0027] The present invention will be further described below in conjunction with specific embodiments, and it should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various modifications or changes to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the application.
[0028] The materials used in the embodiments of the present invention are shown in the following table.
[0029]
[0030]
[0031] Example 1
[0032] (1) Grubbs second-generation catalyst and cyclohexylbenzene were prepared at a mass ratio of 1:100, and the temperature was raised to 60°C. After 1 hour, the catalyst was completely dissolved, and then a retarder was added at a molar ratio of catalyst to tributyl phosphite of 1:1. The catalyst solution was placed at room temperature for use. Based on a molar ratio of catalyst to DCPD monomer of 1:10000, the above catalyst solution was added to dicyclopentadiene mixed with 5% norbornene, and the dicyclopentadiene resin system was prepared.
[0033] (2) E51 epoxy resin, methyltetrahydrophthalic anhydride and ethylenediamine alcohol are mixed and stirred in a mass ratio of 100:50:10, and the epoxy resin system is configured.
[0034] (3) The dicyclopentadiene resin system prepared in (1) and the epoxy resin prepared in (2) are prepared in a mass ratio of 100:5, and mixed and stirred evenly to obtain the mixed resin system prepared in the present invention.
[0035] The mixed resin system prepared in Example 1 was cured, and the degree of curing was tested by DCS according to HB 7614-1998. At 90°C, the degree of curing reached 90% after curing for 3 minutes. After post-curing at 120°C for one hour, DSC showed that there was no curing exothermic peak, but only one glass transition temperature (147.3°C), indicating that the mixed resin had been completely cured.
[0036] The composite material was prepared by wet molding process, the mixed resin system was coated on the carbon fiber, and then put into the molding machine to maintain pressure (0.2MPa) and temperature (90℃) for three minutes, then taken out and put into 120℃ oven for 1 hour. The carbon fiber specification is T300, plain cloth, and the surface density is 200gsm. According to ASTM D2344 standard, the interlaminar shear strength of the mixed resin and carbon fiber was tested, and the result was 37.9MPa.
[0037] Example 2
[0038] (1) Grubbs second-generation catalyst and cyclohexylbenzene were prepared at a mass ratio of 1:200, and the temperature was raised to 45°C. After half an hour, the catalyst was completely dissolved, and then a retarder was added at a molar ratio of catalyst to tributyl phosphite of 1:2. The catalyst solution was placed at room temperature for use. Based on a molar ratio of catalyst to DCPD monomer of 1:5000, the above catalyst solution was added to dicyclopentadiene mixed with 3% norbornene, and the dicyclopentadiene resin system was prepared. (2) E51 epoxy resin was mixed with methyl hexahydrophthalic anhydride and triethanolamine at a mass ratio of 100:25:5, and the epoxy resin system was prepared.
[0039] (3) The dicyclopentadiene resin system prepared in (1) and the epoxy resin prepared in (2) are prepared in a mass ratio of 100:5, and mixed and stirred evenly to obtain the mixed resin system prepared in the present invention.
[0040] The mixed resin system prepared in Example 2 was cured, and the degree of curing was tested by DCS according to HB 7614-1998. At 60°C, the degree of curing reached 92% after 3 minutes of curing. After one hour of post-curing at 120°C, DSC showed that there was no curing exothermic peak, and only one glass transition temperature (148.6°C), indicating that the mixed resin had been completely cured.
[0041] The composite material was prepared by wet molding process, the mixed resin system was coated on the glass fiber, and then put into the molding machine to maintain pressure (0.2MPa) and temperature (60℃) for three minutes, then taken out and put into 120℃ oven for 1 hour. The glass fiber specification is alkali-free plain cloth with a surface density of 800gsm. According to ASTM D2344 standard, the interlayer shear strength of the mixed resin and glass fiber was tested, and the result was 36.4MPa.
[0042] Example 3
[0043] (1) Grubbs second-generation catalyst and cyclohexylbenzene were prepared at a mass ratio of 1:200, and the temperature was raised to 45°C. After half an hour, the catalyst was completely dissolved, and then the retarder was added at a molar ratio of catalyst to tributyl phosphite of 1:4. The catalyst solution was placed at room temperature for use. Based on a molar ratio of catalyst to DCPD monomer of 1:5000, the above catalyst solution was added to dicyclopentadiene mixed with 3% norbornene, and the dicyclopentadiene resin system was prepared. (2) E51 epoxy resin, methyl nadic anhydride and DMP-30 were mixed and stirred at a mass ratio of 100:70:5, and the epoxy resin system was prepared.
[0044] (3) The dicyclopentadiene resin system prepared in (1) and the epoxy resin prepared in (2) are prepared in a mass ratio of 100:10, and mixed and stirred evenly to obtain the mixed resin system prepared in the present invention.
[0045] The mixed resin system prepared in Example 3 was cured, and the degree of curing was tested by DCS according to HB 7614-1998. At 90°C, the degree of curing reached 91% after curing for 5 minutes. After post-curing at 150°C for 2 hours, DSC showed that there was no curing exothermic peak, but only one glass transition temperature (154.7°C), indicating that the mixed resin had been completely cured.
[0046] The composite material was prepared by wet molding process, the mixed resin system was coated on the basalt fiber, and then put into the molding machine to maintain pressure (0.2MPa) and temperature (90℃) for 5 minutes, then taken out and put into 150℃ oven for 2 hours. The basalt specification is plain weave cloth with a surface density of 583gsm. According to ASTM D2344 standard, the interlayer shear strength of the mixed resin and basalt fiber was tested, and the result was 32.9MPa.
[0047] Example 4
[0048] (1) Grubbs second-generation catalyst and cyclohexylbenzene were prepared at a mass ratio of 1:300, and the temperature was raised to 45°C. After half an hour, the catalyst was completely dissolved, and then a retarder was added at a molar ratio of catalyst to tributyl phosphite of 1:5. The catalyst solution was placed at room temperature for use. Based on a molar ratio of catalyst to DCPD monomer of 1:5000, the above catalyst solution was added to dicyclopentadiene mixed with 3% norbornene, and the dicyclopentadiene resin system was prepared. (2) E51 epoxy resin, methyl nadic anhydride and DMP-30 were mixed and stirred at a mass ratio of 100:40:10, and the epoxy resin system was prepared.
[0049] (3) The dicyclopentadiene resin system prepared in (1) and the epoxy resin prepared in (2) are prepared in a mass ratio of 100:5, and mixed and stirred evenly to obtain the mixed resin system prepared in the present invention.
[0050] The mixed resin system prepared in Example 4 was cured, and the degree of curing was tested by DCS according to HB 7614-1998. At 90°C, the degree of curing reached 92% after curing for 5 minutes. After post-curing at 150°C for 1 hour, DSC showed that there was no curing exothermic peak, but only one glass transition temperature (148.7°C), indicating that the mixed resin had been completely cured.
[0051] The composite material was prepared by wet molding process, the mixed resin system was applied on the carbon fiber, and then put into the molding machine to maintain pressure (0.2MPa) and temperature (90℃) for 5 minutes, then taken out and put into 150℃ oven for 1 hour. The carbon fiber specification is 3K plain cloth with a surface density of 300gsm. According to ASTM D2344 standard, the interlayer shear strength of the mixed resin and carbon fiber was tested, and the result was 40.9MPa.
[0052] Example 5
[0053] (1) Grubbs second-generation catalyst and cyclohexylbenzene were prepared at a mass ratio of 1:100, heated to 60°C, and the catalyst was completely dissolved after 1 hour. Then, a retarder was added at a molar ratio of catalyst to tributyl phosphite of 1:8, and the catalyst solution was placed at room temperature for use. Based on a molar ratio of catalyst to DCPD monomer of 1:5000, the above catalyst solution was added to dicyclopentadiene mixed with 3% norbornene, and the dicyclopentadiene resin system was prepared. (2) E51 epoxy resin, methyltetrahydrophthalic anhydride and DMP-30 were mixed and stirred at a mass ratio of 100:25:10, and the epoxy resin system was prepared.
[0054] (3) The dicyclopentadiene resin system prepared in (1) and the epoxy resin prepared in (2) are prepared in a mass ratio of 100:5, and mixed and stirred evenly to obtain the mixed resin system prepared in the present invention.
[0055] The resin prepared in Example 5 can reach a degree of curing of 95% using DSC at 90° C. for 5 minutes, and can be fully cured by post-curing at 120° C. for 1 hour.
[0056] The mixed resin system prepared in Example 5 was cured, and the degree of curing was tested by DCS according to HB 7614-1998. At 90°C, the degree of curing reached 95% after curing for 5 minutes. After post-curing at 120°C for 1 hour, DSC showed that there was no curing exothermic peak, but only one glass transition temperature (142.8°C), indicating that the mixed resin had been completely cured.
[0057] The composite material was prepared by wet molding process, the mixed resin system was coated on the carbon fiber, and then put into the molding machine to maintain pressure (0.2MPa) and temperature (90℃) for 5 minutes, then taken out and put into 120℃ oven for 1 hour. The carbon fiber specification is 3K plain cloth with a surface density of 300gsm. According to ASTM D2344 standard, the interlaminar shear strength of the mixed resin and carbon fiber was tested, and the result was 44.9MPa.
[0058] Example 6
[0059] (1) Grubbs second-generation catalyst and cyclohexylbenzene are prepared at a mass ratio of 1:400, and the temperature is raised to 40°C. After half an hour, the catalyst is completely dissolved, and then a retarder is added at a molar ratio of catalyst to tributyl phosphite of 1:8. The catalyst solution is placed at room temperature for use. Based on a molar ratio of catalyst to DCPD monomer of 1:5000, the above catalyst solution is added to dicyclopentadiene mixed with 3% norbornene, and the dicyclopentadiene resin system is prepared. (2) Bisphenol S epoxy resin, phthalic anhydride and triethanolamine are mixed and stirred at a mass ratio of 100:55:10, and the epoxy resin system is prepared.
[0060] (3) The dicyclopentadiene resin system prepared in (1) and the epoxy resin prepared in (2) are prepared in a mass ratio of 100:10, and mixed and stirred evenly to obtain the mixed resin system prepared in the present invention.
[0061] The mixed resin system prepared in Example 6 was cured, and the degree of curing was tested by DCS according to HB 7614-1998. At 90°C, the degree of curing reached 91% after curing for 5 minutes. After post-curing at 150°C for 1 hour, DSC showed that there was no curing exothermic peak, but only one glass transition temperature (152°C), indicating that the mixed resin had been completely cured.
[0062] The composite material was prepared by wet molding process, the mixed resin system was applied on the carbon fiber, and then put into the molding machine to maintain pressure (0.2MPa) and temperature (90℃) for 5 minutes, then taken out and put into 150℃ oven for 1 hour. The carbon fiber specification is 3K plain cloth with a surface density of 200gsm. According to ASTM D2344 standard, the interlayer shear strength of the mixed resin and carbon fiber was tested, and the result was 46.5MPa.
[0063] Example 7
[0064] (1) Grubbs second-generation catalyst and cyclohexylbenzene were prepared at a mass ratio of 1:200, and the temperature was raised to 60°C. After 1 hour, the catalyst was completely dissolved, and then a retarder was added at a molar ratio of catalyst to tributyl phosphite of 1:4. The catalyst solution was placed at room temperature for use. Based on a molar ratio of catalyst to DCPD monomer of 1:5000, the above catalyst solution was added to dicyclopentadiene mixed with 4% norbornene, and the dicyclopentadiene resin system was prepared.
[0065] (2) Bisphenol F resin F170, methyltetrahydrophthalic anhydride and DMP-30 are mixed and stirred at a mass ratio of 100:60:5, and the epoxy resin system is prepared.
[0066] (3) The dicyclopentadiene resin system prepared in (1) and the epoxy resin prepared in (2) are prepared in a mass ratio of 100:10, and mixed and stirred evenly to obtain the mixed resin system prepared in the present invention.
[0067] The mixed resin system prepared in Example 7 was cured, and the degree of cure was tested by DCS according to HB 7614-1998. At 90°C, the degree of cure reached 92% after 5 minutes of curing. After 1 hour of post-curing at 150°C, DSC showed that there was no curing exothermic peak, but only one glass transition temperature (140°C), indicating that the mixed resin had been completely cured.
[0068] The composite material was prepared by wet molding process, the mixed resin system was coated on the carbon fiber, and then put into the molding machine to maintain pressure (0.2MPa) and temperature (90℃) for 5 minutes, then taken out and put into 150℃ oven for 1 hour. The carbon fiber specification is 3K plain cloth with a surface density of 200gsm. According to ASTM D2344 standard, the interlayer shear strength of the mixed resin and carbon fiber was tested, and the result was 41.5MPa.
Claims
1. A method for preparing a fast-curing modified polydicyclopentadiene resin, comprising the following steps: (1) Preparation of polydicyclopentadiene resin system: dissolving Grubbs II catalyst and tributyl phosphite in cyclohexylbenzene to prepare a catalyst solution, and mixing the prepared catalyst solution with dicyclopentadiene or norbornene-dicyclopentadiene mixed solution; (2) Epoxy resin system preparation: Add anhydride curing agent and accelerator to epoxy resin and mix thoroughly; (3) mixing the epoxy resin system prepared in step (2) and the polydicyclopentadiene resin system prepared in step (1), stirring and mixing them evenly and then storing them at room temperature to obtain the modified polydicyclopentadiene resin; In the step (1), the molar ratio of the Grubbs second-generation catalyst to dicyclopentadiene is 1:5000 to 1:15000, the molar ratio of the second-generation catalyst to tributyl phosphite is 1:1 to 1:8, and the mass ratio of the second-generation catalyst to cyclohexylbenzene is 1:100 to 1:400; In the step (3), the mass ratio of the epoxy resin system to the polydicyclopentadiene resin system is 5:100 to 10:
100.
2. The method according to claim 1, characterized in that The epoxy resin in step (2) comprises at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, and bisphenol S epoxy resin; the acid anhydride curing agent is selected from at least one of methyl nadic anhydride, methyl tetrahydrophthalic anhydride, methyl hexahydrophthalic anhydride, and phthalic anhydride; and the accelerator is selected from at least one of 2, 4, 6-tris(dimethylaminomethyl)phenol, benzyldimethylamine, and triethanolamine.
3. The method according to claim 2, characterized in that In step (2), the amount of the accelerator is 5wt% to 10wt% of the epoxy resin; The amount of anhydride curing agent in step (2) satisfies the following formula: W=A e ×B×N and N=0.2~1.0, Wherein, W is the mass of anhydride curing agent required per 100g epoxy resin, g; A e is the molar mass of the anhydride, kg / mol; B is the epoxy value of the epoxy resin; N is the amount of anhydride required per molar mass of epoxy group, mol.
4. The method according to claim 3, characterized in that The norbornene-dicyclopentadiene mixed solution in step (1) contains 3% to 5% by mass of norbornene.
5. The method according to claim 4, characterized in that In the step (1), the dissolution temperature of the Grubbs second-generation catalyst in cyclohexylbenzene is 40 to 60° C., and the dissolution time is 30 to 60 minutes.
6. A fast-curing modified polydicyclopentadiene resin prepared by any one of the preparation methods described in claims 1 to 5.
7. Use of the fast-curing modified polydicyclopentadiene resin according to claim 6 in preparing fiber composite materials.
8. The use according to claim 7, characterized in that: The modified polydicyclopentadiene resin is coated on the fiber, and then placed in a molding machine for pressure maintenance and curing, and then placed in an oven for heat treatment to obtain a fiber composite material, wherein the fiber is selected from At least one of carbon fiber, glass fiber, and basalt fiber, wherein the curing is maintained at 60°C to 90°C for 3 to 5 minutes, The heat treatment is carried out at 120-150° C. for 1-2 hours.
Citation Information
Cited By
Method for ultrafast impregnation packaging of superconducting structure
CN120265108A
High-damping machine tool moving part and preparation method thereof
CN122234566A